A history of violence - Wagner, John 1949-; Locke, Vince 1966- (Vertigo Crime, 1997)
Tom McKenna owns a diner in a small town. He foils a robbery and becomes famous ... maybe too famous. The attention now focused on Tom brings up questions about his past
"The original graphic novel"--Cover
"A graphic mystery"--Page 4 of cover
Keywords: Organisiertes Verbrechen; Gangster; Restaurant; Verwechslung; Raub; Gewaltkriminalität; Indiana; Gangsters / United States / Comic books, strips, etc; Organized crime / United States / Comic books, strips, etc; Gangsters / États-Unis / Bandes dessinées; Crime organisé / États-Unis / Bandes dessinées; Gangsters; Organized crime; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; Suspense comic books, strips, etc; Comics (Graphic works); Graphic novels; Mystery comic books, strips, etc; Comic